Using genetic Algorithm in Task scheduling for Multiprocessing System - Asmaa Hammo; Ghosun Basheer; Muna Jawhar (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this work we use Genetic Algorithm for best section to implement many independent tasks on multiprocessor systems. The chromosome represented by numbers of integer value, every value represents one of the processors in the system, we use the simple crossover to generate the next population, and we us the mutation of type  partial gen for mutation  which has a good role to improve results of scheduling, the program written by matlab (6.5).The results, after a small number of iterations, were very good .